Saúde mental de jovens adultos: presença da arte e do lazer no cotidiano e na Terapia Ocupacional - Carvalho, Luana Mara Nunes de (Universidade Federal de São Carlos, 2024)
The use of art as a therapeutic tool in Psychosocial Care Centers (CAPS) is widely applied, but how do the users themselves perceive this practice in their daily lives? This raises the need to investigate the presence of art in the daily lives of young people who utilize mental health services and to understand how this artistic interaction influences their treatment processes. Although the scientific literature recognizes the relevance of art in this context, it still lacks deeper analyses from the users' perspectives. The motivation to explore this topic lies in the search for a broader understanding of how art integrates into these young people's lives, their access to cultural and leisure activities, and the role they play in society. Objective: To analyze the impact of art on the mental health of young people served by CAPS, aiming to understand how it contributes to their well-being, its presence in their daily lives, and the participants' perceptions of access to and the significance of art in their lives. Methodology: The present study employed the Photovoice methodology, a participatory and qualitative method that allows participants to reflect on their challenges, visually document these aspects, and share the meanings attributed to the images. This approach promotes a deeper understanding of the issues addressed and facilitates the development of intervention strategies and engagement with policymakers.
Mental health of young adults: presence of art and leisure in everyday life and in Occupational Therapy
Keywords: Arte; Juventude; Saúde mental; Terapia ocupacional; OUTROS